POTENSI PASAR TRADISIONAL SIMABUR BAGI MASYARAKAT DI NAGARI SIMABUR KECAMATAN PARIANGAN KABUPATEN TANAH DATAR (Program Studi Pendidikan Geografi Universitas PGRI Sumatera Barat, 2015)
This research conducted in kenagarian Simabur Pariangan districs Tanah Datar regency, which aims to determine the potential of tradisional market Simabur for people in villages Simabur Pariangan districs Tanah Datar regency both interms of jobs, household incomes and land lease. The type of the research belong to the descriptive study sampling taken technique Proporsional Random Sampling, with a sample of 73 people. The sample is peope there, merchants located around the Simabur market, collecting data though observation and direct observation from the field to the questionnaire. This research resulted in several conclussions : (1) The potential market for employment in the village community in Simabur Pariangan districs Tanah Datar regency to work, on a general merchant, (2) The potential market for the income of the people in the Simabur village Pariangan districs Tanah Datar regency the average income of market than Rp.2.000.000, (3) Potential market for land lease communities in Simabur village Pariangan districs Tanah Datar regency the everage lease for every day is Rp.3000-6000. Keywords : Potential, Market, Communities